Selection of incentives for a business strategy based on crop diversification - Martínez-García, Victor; Zabala, José A.; Albaladejo-García, José A.; López-Becerra, Erasmo; Sánchez-Navarro, Virginia; Sánchez-Navarro, Jorge L.; Boix-Fayos, Carolina; Martínez-Paz, José M.; Alcon, Francisco (Spanish Journal of Agricultural Research, 2024)
Aim of study: This study proposes a crop diversification innovative business model based on stakeholder preferences towards different incentive alternatives.Area of study: South-East Spain.Material and methods: Citrus intercropping practices in South-East Spain has been used as case study. Stakeholders’ preferences for crop diversification incentives were investigated by using a multicriteria approach, and those results were integrated into the development of a business model canvas.Main results: Including crop diversification practices as environmental practices within the operational programmes of producer organizations is seen the most preferred incentive over which the business model canvas is developed.Research highlights: The establishment of business opportunities for crop diversification practices would facilitate the overcoming of adoption barriers along the agrifood value chain and would promote health and sustainable food systems.